Automatic creating test as one of the processing tasks of natural language texts - Мороз, Андрій Віталійович (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of modern technologies for natural text processing is executed. It is shown that in the control knowledge systems it is necessary the use of the systems as a "text-question-answering", and the conceptual elements of such systems creation are offered